GSK-3 Beta Inhibition More Strongly Blocks Acquisition Than Expression of Amphetamine-produced Conditioned Place Preference in Rats - Wickens, Rebekah; Beninger, Richard J. (The Meducator, 2013)
Dopamine (DA) has been implicated in behavioural sensitization and incentive learning. The signaling molecule glycogen synthase kinase-3β (GSK-3β), activated downstream of DA D2-like receptors, affects DA-mediated behaviours. For example, inhibition of GSK-3β attenuates locomotor sensitization to psychomotor stimulant drugs. Few studies have examined the effects of GSK-3β inhibition in incentive learning paradigms. We examined the effects of GSK-3β inhibition on incentive learning produced by amphetamine (1.5 mg/kg) in the conditioned place preference (CPP) paradigm. The selective GSK-3 inhibitor SB 216763 was administered intraperitoneally to male Wistar rats at doses of 1.0, 2.0, and 2.5 mg/kg during the acquisition or expression phase. Due to studies more strongly implicating signaling molecules in acquisition rather than expression of learning, we hypothesized a block of acquisition of CPP at doses that fail to block expression of CPP. Results supported this hypothesis: the 1.0 mg/kg dose of SB 216763 failed to block either acquisition or expression of CPP; the 2.0 mg/kg dose blocked acquisition, but not expression of CPP; and the 2.5 mg/kg dose blocked both acquisition and expression of CPP. These results indicate that inhibiting GSK-3β may attenuate incentive learning differentially in acquisition versus expression of conditioning. (Funded by NSERC)